Writing into design: An embedded writing course for architectural studies - Manià, K.; Janse van Rensburg, A.; Bird, R. (South African Journal of Higher Education, 2017)
Architects must be able to express their ideas clearly to communicate their designs; at the same time graduate professional degree programs demand advanced critical literacy and academic writing skills. Competence in this domain for high school graduates in South Africa often falls short of the expected proficiencies of first-year students at tertiary level. To address this gap, an embedded writing course was integrated into the first-year Design Studio and History of Architecture course. This intervention adopted the approaches provided by writing-intensive pedagogy, successfully improving students’ written expression, and their ability to engage with their architectural studies in deeper and more critical ways.